Synthesis and Characterization of N-(2,3,4,6-Tetra-O-acetyl-β-D-glucopyranosyl) thiocarbamic 2,4-dihydroxy benzoyl hydrazine monohydrate - Li, Xue-Mei; Ye, Su-Juan; Tang, Xu-Li; Ding, Cai-Feng; Zhang, Shu-Sheng (Asian Journal of Chemistry, 2010)
A new complex of N-(2,3,4,6-Tetra-O-acetyl-β-D-glucopyranosyl) thiocarbamic 2,4-dihydroxy benzoyl hydrazine monohydrate, C22H27N3O11S·H2O, has been synthesized and its structure is determined by X-ray crystallography and TG/DTG. The compound crystallizes in the orthorhombic system, space group P43212, with cell dimensions of a = 12.0199 (7), b = 12.0199 (7), c = 38.877 (3) Å, V = 5616.9 (6) Å3 and Z = 8. The hexopyranosyl ring adopts a 4C conformation. All the substituents are in equatorial positions. The molecules are linked into a three-dimensional framework by intermolecular interactions. The atoms O3, O7, O9 and C14 show positional disorders.